Solvothermal synthesis of ZnO-decorated α-Fe2O3 nanorods with highly enhanced gas-sensing performance toward n-butanol - Kaneti; Quadir, Md Zakaria; Zhengjie Zhang; Chuyang Chen; Jeffrey Yue; Minsu Liu; Xuchuan Jiang; Aibing Yu (R S C Publications, 2014)
This paper reports a newly developed solvothermal strategy for the synthesis of ZnO-decorated α-Fe2O3 nanorods based on the reaction of α-Fe2O3 nanorods with zinc sulfate and urea in autoclaves at 180 °C. The resulting nanocomposites consist of porous α-Fe2O3 nanorods with diameters of 100–200 nm and a surface decorated with small ZnO nanoparticles (10–20 nm). The ZnO NPs are found to grow epitaxially on {110} planes of α-Fe2O3, forming an interfacial orientation relationship of (100)ZnO/(110)α-Fe2O3. The addition of ZnO is found to shift the Fe 2p peak position in the α-Fe2O3/ZnO nanocomposites to higher binding energies due to the formation of the α-Fe2O3/ZnO heterojunction interface. The gas-sensing results show that the ZnO-decorated α-Fe2O3 nanorods exhibit excellent sensitivity, selectivity, and stability toward n-butanol gas at a low optimum temperature of 225 °C. In particular, they show higher sensitivity compared to pure α-Fe2O3 (4 times higher) and ZnO nanorods (2.5 times higher), respectively, along with faster response times. The significant enhancement in sensitivity may be attributed to the chemical and electronic sensitization induced by the ZnO nanoparticles deposited on the surfaces of the α-Fe2O3 nanorods. The findings reported in this study will be useful for the design and construction of surface modified-metal oxide nanostructures with enhanced gas-sensing performance.